Pemberian Sanksi Administrasi Aparatur Sipil Negara Yang Melanggar Disiplin Di Pemerintah Kota Mojokerto - Anggraini, Novellita Sicillia; Rohmatiah, Ahadiati (Universitas Merdeka Madiun, 2019)
The purpose of this study is untuk know and analyze implementation of administrative sanctions against the Civil Servant who commit disciplinary offenses; and to identify obstacles in administrative disciplinary sanctions on the Government of the State Civil Apparatus Mojokerto.This research was conducted in Mojokerto. As for the object of research is the Regional Employment Board Mojokerto. This research was conducted by direct interviews dengannarasumber research sites and relevant competent dengantopik proposed. The second approach is to memaparkansecara deskriprif various interviews and then do analisisterhadap data.The results of this study showed that the general implementation of sanctions in Mojokerto city government has not sepenuhnyamengikuti Government Regulation No. 53 of 2010. The administrative disciplinary sanctions in the State Civil Apparatus in Mojokerto still often get kendaladan barriers such as the length of the process to be followed in the provision of such sanctions , Omission committed by the employer for violations of discipline by the State Civil Apparatus and lack of awareness of the State Civil Apparatus in doing his duty as a servant of the state and public servant